Analysis and improvement of fourth‐order generalised integrator based phase‐locked loop. Issue 2 (30th December 2020) - Li, Jinbo; Wang, Qin; Xiao, Lan; Lu, Yichen; Wu, Qunfang
Abstract: The fourth‐order generalised integrator is very suitable for single‐phase phase‐locked loop because it can provide orthogonal signal conveniently and block harmonic voltages effectively. In the conventional fourth‐order generalised integrator based phase‐locked loop, the resonance frequency of fourth‐order generalised integrator needs to be adjusted according to the grid frequency. To improve the phase‐locked loop performance, a non‐adaptive fourth‐order generalised integrator is suggested for single‐phase system, and this paper presents a correction method. According to the estimated grid frequency, the amplitude imbalance and phase error caused by non‐adaptive fourth‐order generalised integrator can be calculated, and two adaptive units are added to deal with the problems. Moreover, the small‐signal model of the proposed phase‐locked loop is carried out, and the control parameters are tuned. Compared to conventional fourth‐order generalised integrator based phase‐locked loop, the proposed phase‐locked loop shows a better performance, which is verified through simulation and experimental results.